Immobilization of Dextranase Using Anionic Natural Polymer Alginate as a Matrix for the Degradation of a Long-Chain Biopolymer (Dextran) - Faiza Shahid; Afsheen Aman; Shah Ali Ul Qader (International Journal of Polymer Science)
Alginate is an inexpensive, nontoxic, valuable biopolymer utilized in the study for the immobilization of commercially applicable biocatalyst dextranase. Dextranase was immobilized by an entrapment method, and alginate hydrogel spheres were synthesized after optimizing several parameters. A sodium alginate concentration of 4.0% was noticed to be suitable along with a calcium chloride concentration of 0.2 molar after providing a curing time of 20 minutes. After comparing the characteristics of the entrapped enzyme with those of the soluble one, it was observed that the characteristics were more or less the same except for the change in reaction time which was noticed to be prolonged in the case of entrapped dextranase while the change in temperature and pH optima was not observed. The variation in Vmax and Km values of dextranase after entrapment was also noted. However, after extensive stability examination studies, it was found that dextranase became more stable after entrapment; as a result, it retained more than 50% of its original activity at elevated temperature even after exposure for about 2.0 hours. The reusability of dextranase was up to 7.0 cycles after performing catalytic activity under constant condition.